Obstacle avoidance with fuzzy logic controller - Orillo, John William F. (Animo Repository, 2010)
This study presents a simulated obstacle avoiding robot by fuzzy logic implementation. The basic goal of the simulated robot is to reach the target and avoid the obstacles along its path. The movement of the robot and avoidance characteristics is then guided by mathematical calculations fuzzyfication, and diffuzification. Also dynamic obstacles are included in the simulation to test the robustness and accuracy of the program. The speed, angle, and movement of the robot are dependent on FAM and the fuzzified data. The program is then simulated by using a graphical user interface done in c#. After several testing of the simulator the program showed 95% accuracy and thus concluded to be robust.